Maturity-Onset Diabetes of the Young (MODY): Genetic Causes, Clinical Characteristics, Considerations for Testing, and Treatment Options - Zoltan Antal (Endocrines, 2021)
Maturity Onset Diabetes of the Young (MODY) encompasses a group of rare monogenic forms of diabetes distinct in etiology and clinical presentation from the more common forms of Type 1 (autoimmune) and Type 2 diabetes. Since its initial description as a clinical entity nearly 50 years ago, the underlying genetic basis for the various forms of MODY has been increasingly better elucidated. Clinically, the diagnosis may be made in childhood or young adulthood and can present as overt hyperglycemia requiring insulin therapy or as a subtle form of slowly progressive glucose impairment. Due to the heterogeneity of clinical symptoms, patients with MODY may be misdiagnosed as possessing another form of diabetes, resulting in potentially inappropriate treatment and delays in screening of affected family members and associated comorbidities. In this review, we highlight the various known genetic mutations associated with MODY, clinical presentation, indications for testing, and the treatment options available.